Same DNA, same location, same price? Price differences across distribution e-channels of a single online retailer - Vladimir Fedoseev; Svetlana Fedoseeva (Agribusiness, 2022)
Although price dispersion remains a prominent feature of international and domestic markets, the development of e-commerce has been increasingly promoting uniform pricing. Existing studies suggest that online competition, especially from Amazon, reduces price dispersion within individual retailer's chains and among stores in different chains. Although Amazon's effect on the rivals have been analyzed, little is known about its pricing across own distribution channels. Do pricing strategies differ among Amazon's online channels within a single geographical market? We use a large dataset on grocery price quotes from Amazon's main platform and its subsidiary Amazon Fresh in Berlin, Germany, to test whether those (both pure online) channels apply deviating pricing strategies. Our results indicate that Amazon's channels partially set unequal prices for overlapping parts of the assortment, focus on assortments with different average unit values, and vary in their application of price promotions.[EconLit Citations: E31, L11, M31, Q11].
Keywords: 630; e-commerce; e-marketplaces; online food retailing; price dispersion